kualitas pengelolaan dana ZIS oleh lembaga Ziswaf: pengaruhnya terhadap kepercayaan masyarakat - Muhammad Zikri rizwadi; Nadine Martha logawa; Nadia salsabilla Hidayat putri; Renatha Fatma olyvia (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the influence of the quality of Zakat, Infak, and Sadaqah (ZIS) fund management by Ziswaf institutions on public trust levels. Quality management, including transparency, accountability, and professionalism, is a key factor in building and maintaining donor trust. This literature review collects and analyzes various recent sources (2020-2025) discussing ZIS fund management and public trust. The findings show that institutions that manage funds effectively, supported by information technology and transparent reporting systems, tend to achieve higher levels of public trust. This trust positively impacts the increased participation of muzakki in fulfilling zakat and sadaqah obligations through official institutions. Therefore, Ziswaf institutions need to continuously improve internal management and public communication to enhance the sustainability of ZIS fund management.